2020
DOI: 10.1055/s-0040-1714719
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in COVID-19 Positive Neonates and Possibility of Viral Vertical Transmission: A Narrative Review

Abstract: Objective Novel coronavirus disease 2019 (COVID-19) seems to affect adults and pediatric patients differently. While neonates are a special population, little is known about the neonatal outcomes. This study aimed to investigate the outcomes in COVID-19 positive neonates and incidence of vertical transmission of the virus by reviewing available literature. Study Design This study is a narrative review of available literature on “COVID-19 in neonates,” for which PubMed and Google Scholar were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 52 publications
4
36
1
2
Order By: Relevance
“…Furthermore, the report suggested the resemblance of clinical spectrum in neonates to adult population; however, the outcomes were more favorable [3]. Another review of 23 SARS-CoV-2-positive neonates found a male predominance and prematurity in one-third of cases [4].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, the report suggested the resemblance of clinical spectrum in neonates to adult population; however, the outcomes were more favorable [3]. Another review of 23 SARS-CoV-2-positive neonates found a male predominance and prematurity in one-third of cases [4].…”
Section: Introductionmentioning
confidence: 98%
“…Laboratory investigations in neonates with COVID-19 were often normal, though leucopenia or leukocytosis, lymphopenia, and raised lactate dehydrogenase (LDH) and creatine kinase (CK) have been reported [4,5]. A large review on neonatal COVID-19 described lymphopenia (14.4%) and transaminitis (4.1%) and raised inflammatory markers (Creactive protein) (15.5%) [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open access transmission in neonates with SARS-CoV-2 published in the literature. [11][12][13][14] The American Academy of Pediatrics (AAP) neonatal-perinatal COVID-19 registry update of 3 October 2020 reported that, among 3722 mother/infant dyads and 3359 COVID-19 positive mothers, only 52 (1.6%) of 3198 infants tested positive for SARS-CoV-2. 15 Social distancing and wearing face masks/coverings have been shown to mitigate the spread of viral transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Rekomendasi AAP untuk petugas medis agar menggunakan alat pelindung diri selama resusitasi neonatus termasuk gaun, sarung tangan, masker pernapasan N 95, dan kacamata pelindung mata atau alat bantu pernapasan penyaring udara. 8 Penerapan protokol pencegahan infeksi yang ketat saat periode perinatal dapat mengurangi insiden penularan horizontal virus COVID-19 secara bermakna. 7 Penularan melalui kontak kulit-ke-kulit masih kontroversial sehingga kontak kulit-ke-kulit dapat diizinkan jika ibu menggunakan masker dan mencuci tangan.…”
unclassified